Fetal Origin of Sensorimotor Behavior - Fagard, Jaqueline; Esseily, Rana; Jacquey, Lisa; O’Regan, Kevin; Somogyi, Eszter (Frontiers in Neurorobotics, 2018)
The aim of this article is to track the fetal origin of infants’ sensorimotor behavior. We consider development as the self-organizing emergence of complex forms from spontaneously generated activity, governed by the innate capacity to detect and memorize the consequences of spontaneous activity (contingencies), and constrained by the sensory and motor maturation of the body. In support of this view, we show how observations on fetuses and also several fetal experiments suggest that the fetus's first motor activity allows it to feel the space around it and to feel its body and the consequences of its movements on its body. This primitive motor babbling gives way progressively to sensorimotor behavior which already possesses most of the characteristics of infants’ later behavior: repetition of actions leading to sensations, intentionality, some motor control and oriented reactions to sensory stimulation. In this way the fetus can start developing a body map and acquiring knowledge of its limited physical and social environment.